La implementación de la narrativa digital como herramienta para mejorar la destreza de escuchar entre los estudiantes del séptimo año de educación básica de la escuela Zoila Alvarado de Jaramillo en la ciudad de Loja, durante el periodo académico 2014 - 2015 - Alvarado Sarango, Diana Elizabeth (2016)
The present research work was carried out to implement digital storytelling as a tool to improve listening skills with students of seventh year of Basic Education at "Zoila Alvarado Jaramillo" School in Loja city, during the academic period 2014-2015. To perform this research work, the scientific, descriptive, analytic-synthetic and statistical methods were used to develop the analysis and process the information. In addition to that, tests and questionnaires were applied before and after the intervention to thirty students as instruments to gather the necessary information about the level that students had in listening and their opinions on the use of digital storytelling in the class. The main results of the analysis of the post-test were that the implementation of digital storytelling as a tool had a positive effect in the improvement of students’ listening skill in their ability to listen comprehensively and in identifying specific details. They were able to listen in a comprehensive way and identify specific details. The main conclusion was that digital storytelling helped students not only to improve their listening skills but also motivated them to listen carefully the English classes.